Quotation as a Key to the Investigation of Ideological Manipulation in News Trans-Editing in the Taiwanese Press - Chen, Ya-mei (TTR, 2009)
News trans-editing, which has gate-keeping and adaptation as distinctive features, is widely adopted by news organizations to produce suitable target texts. Since news organizations are socially, politically and economically situated, news trans-editing is always mediated in one way or another. Using the trans-editing of quotation as a key, this paper conducts an empirical case study and investigates how the target newspapers’ ideologies systematically manipulate the seemingly “objective” trans-edited news texts.The case study data covers some news texts concerning China’s anti-secession law from the New York Times and the Washington Post, and their trans-edited Chinese versions from the China Times, the United Daily News and the Liberty Times in Taiwan. After introducing the relevant contextual factors, a comparative study of the source and target texts is made in terms of the following four aspects of quotation to identify recurrent shifts: quotation modes, news sources, quotation contents and reporting verbs. By analyzing ideological reasons behind the recurrent shifts against the contextual factors, this paper elaborates on the target newspapers’ ideological manipulation with practical examples.